Bosquet des malades - Admiration des œuvres de Dieu Paroles et silence d'une femme dans la Castille du XVe siècle - Carthagène, Thérèse de (Sources, 2021)
This book offers the first critical translation into French of the two treatises composed by Teresa de Cartagena in the late 15th century, the Grove of the Infirm and the Wonder at the Works of God. They are the oldest surviving texts written by a female hand in the Castilian vernacular. Their content is strikingly original: the first one is a consolatory treatise in which the author, having become deaf, values illness and disability; the second one is a work of literary polemic in which she defends her authorship as a woman. Famous and well-studied since the 1970s in the Spanish and English-speaking scholarship, they remain little known in the French-speaking world. They come with an introduction that summarizes the lavish bibliography and provides some additional elements of context coming from the examination of the only surviving manuscript.